2017
DOI: 10.1371/journal.pone.0172134
|View full text |Cite|
|
Sign up to set email alerts
|

Examining the relationship between socio-economic status, WASH practices and wasting

Abstract: Childhood wasting is a global problem and is significantly more pronounced in low and middle income countries like Bangladesh. Socio Economic Status (SES) and Water, Sanitation and Hygiene (WASH) practices may be significantly associated with wasting. Most previous research is consistent about the role of SES, but the significance of WASH in the context of wasting remains ambiguous. The effect of SES and WASH on weight for length (WHZ) is examined using a Structural Equation Model (SEM) to explicitly describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
7
26
3
Order By: Relevance
“…We found a positive linear association where the z-score for WAZ increased consistently with increase in sanitation coverage. Our study failed to find an association between sanitation coverage and WHZ z-score, in contrast to earlier studies in Nepal [11] and Bangladesh [43] where positive associations were reported. It should be noted that in the supplementary analysis where we modelled childhood wasting (dichotomized version of WHZ zscore using the WHO reference population), cluster sanitation coverage was significantly associated with decreased likelihood of wasting (Supplementary Table 2).…”
Section: Discussioncontrasting
confidence: 99%
“…We found a positive linear association where the z-score for WAZ increased consistently with increase in sanitation coverage. Our study failed to find an association between sanitation coverage and WHZ z-score, in contrast to earlier studies in Nepal [11] and Bangladesh [43] where positive associations were reported. It should be noted that in the supplementary analysis where we modelled childhood wasting (dichotomized version of WHZ zscore using the WHO reference population), cluster sanitation coverage was significantly associated with decreased likelihood of wasting (Supplementary Table 2).…”
Section: Discussioncontrasting
confidence: 99%
“…We found a positive linear association where the z-score for WAZ increased consistently with increase in sanitation coverage. Our study failed to find an association between sanitation coverage and WHZ z-score, in contrast to earlier studies in Nepal (11) and Bangladesh (43) where positive associations were reported. It should be noted that in the supplementary analysis where we modelled childhood wasting (dichotomized version of WHZ z-score using the WHO reference population), cluster sanitation coverage was significantly associated with decreased likelihood of wasting (Supplementary Table 1).…”
Section: Supplementary Analysiscontrasting
confidence: 99%
“…Diarrhoea and infections are widely reported to be significantly associated with wasting and underweight among children in various countries [21,29]. In comparison to this study, various studies in different countries proved that younger children are at more risk of wasting compared to older children like in Myanmar [30] and Bangladesh [19,31].…”
Section: Discussionsupporting
confidence: 40%
“…A large proportion of these diseases are related to diarrhea incidences which contribute to the mortality rate of about 1.9 million and new diarrhea cases estimated at 4 billion annually, especially among children under five years old [16]. Previous literature has shown considerable effects of inappropriate water sanitation and hygiene practices on children undernutrition including wasting in various countries [17][18][19]. However, very few and limited studies in Tanzania [7,20] have evaluated the WASH among sub-groups of population.…”
Section: Introductionmentioning
confidence: 99%